Managing Risk in a Workplace Bicycle Pool - C Rissel; B Telfer (Journal of Road Safety)
The health benefits of cycling are greater than the risk of injury. For organisations to promote cycling through workplace related activities, a risk assessment and risk management plan is necessary. This paper describes how the risks associated with establishing a bicycle pool were managed, to facilitate cycling by staff for work-related activities. This includes conducting a risk assessment, developing control strategies for hazards identified and writing a bicycle use policy. Specific bicycle pool procedures were developed which include health screening and checking bicycle-riding proficiency of potential users. This package of policies and procedures supports organisations in encouraging cycling by staff within a risk management framework.